Investigation of the antimicrobial and antifungal activities of some 1,2,4-triazole derivatives - Frolova, Y. S.; Kaplaushenko, A. H.; Sameliuk, Y. H.; Romanina, D. M.; Morozova, L.; Фролова, Юлія Сергіївна; Каплаушенко, Андрій Григорович; Самелюк, Юрій Геннадійович; Романіна, Дар'я Михайлівна (My University, 2022)
This article presents the results of the study of the antimicrobial and antifungal properties among 1,2,4-triazole derivatives synthesized at the Department of Physical and Colloidal Chemistry of the Zaporizhzhia State Medical University. Previous studies have established the antimicrobial and antifungal activity of 1,2,4-triazole derivatives. Therefore, it was reasonable to investigate highly effective substances with antimicrobial and antifungal properties among synthesized compounds. In the first stage of our research, acute toxicity prediction was performed. The antimicrobial and antifungal properties were carried out by the method of “serial dilutions” on a liquid nutrient. Forty-seven compounds of the different classes were studied for these types of activities. According to our research, derivatives of 3-amino-1,2,4-triazole showed better performance than 3-thio-1,2.4-triazoles for Staphylococcus aureus and Candida albicans. 5-(1Н-tetrazole-1-іl)methyl-4Н- -1,2,4-triazole-3-yl-1-(5-nitrofuran-2-yl)methanimin (11.6) was showed the greatest antimicrobial and antifungal activity. Deeper research for compound 11.6 was done by diffusion in agar (method of “wells”). Studies have shown that molecule 11.6 showed antimicrobial and antifunga action to the studied test strains at a concentration of 2 μg/ml. Hence, this compound can be developed as a helpful therapeutic agent after establishing its safety pharmacology and toxicity.
Keywords: 1,2,4-triazole; antimicrobial activity; antifungal activity